PENGARUH UKURAN PERUSAHAAN, DEBT TO EQUITY RATIO, PROFITABILITAS DAN KEPEMILIKAN SAHAM INSTITUSIONAL PADA PERATAAN LABA - Suryani, Ayu Dewi; Damayanti, Eka (E-Jurnal Akuntansi, 2015)
800x600 The company’s activity can’t be spared from the agency conflict between management (agent) and shareholder (principal) which is the impact of the differences in the interests of the two sides. The preassure to meet the targeted performance urged mangers to do strategies that will increase income of his company. The observasion is done at the company’s manufacturing at Indonesia stock exchange during 2010-2013. Overall observations of 15 companies selected through purposive sampling. Eckel index is used as an indicator of the classification distinguishing between did or didn't make income smoothing. Binary logistic of regression for to test the hypothesis. The results conclude that the only debt-to-equity ratio effect. Three other independent variables showed no effect. Normal 0 false false false IN X-NONE X-NONE MicrosoftInternetExplorer4
Keywords: size, debt to equity ratio, profitability, and institutional stock ownership, income smoothing